The effect of weathering on per- and polyfluoroalkyl substances (PFASs) from durable water repellent (DWR) clothing. (June 2020) - van der Veen, Ike; Hanning, Anne-Charlotte; Stare, Ann; Leonards, Pim E.G.; de Boer, Jacob; Weiss, Jana M.
Abstract: To assess the effects of weathering on per- and polyfluoroalkyl substances (PFASs) from durable water repellent (DWR) clothing, thirteen commercial textile samples were exposed to elevated ultra violet (UV) radiation, humidity, and temperature in an aging device for 300 h, which mimics the lifespan of outdoor clothing. Before and after aging, the textile samples were extracted and analysed for the ionic PFASs (perfluoroalkyl acids (PFAAs), perfluorooctane sulfonamide (FOSA)) and volatile PFASs (fluorotelomer alcohols (FTOHs), acrylates (FTACs) and methacrylates (FTMACs)). Results showed that weathering can have an effect on PFASs used in DWR of outdoor clothing, both on the PFAS profile and on the measured concentrations. In most weathered samples the PFAA concentrations increased by 5- to more than 100-fold, while PFAAs not detected in the original textiles were detected in the weathered samples. DWR chemistries are based on side-chain fluorinated polymers. A possible explanation for the increase in concentration of the PFAAs is hydrolysis of the fluorotelomer based polymers (FTPs), or degradation of the FTOHs, which are used in the manufacturing of the FTPs. The concentrations of volatile PFASs also increased, by a factor up to 20. Suggested explanations are the degradation of the DWR polymers, making non-extractable fluorines extractable, or the transformation or degradation of unknown precursors. Further research is needed to unravel the details of these processes and to determine the transformation routes. This study shows that setting maximum tolerance limits only for a few individual PFASs is not sufficient to control these harmful substances in outdoor clothing. Graphical abstract: Image 1 Highlights: Outdoor clothing with a durable water repellent layer (DWR) are weathered. Weathering of outdoor clothing can result in an increase in PFAAs of 5-fold or more. Weathering of DWR layer results in an increase in volatile PFASs. Potential degradation pathways of the DWR are discussed. Setting maximum tolerance limits for a few PFASs alone is not sufficient.